Molecular Spectroscopy and Molecular Structure: Commemorative Issue in Honor of Professor Austin J. Barnes on Occasion of his 75th Birthday (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue of Molecules is dedicated to Prof. Austin James Barnes by occasion of his 75th birthday, in acknowledgment of his scientific contributions in the fields of molecular spectroscopy and molecular structure. The Special Issue comprises 12 articles that span a broad range of interests within the fields of molecular spectroscopy and molecular structure, such as hydrogen bonding, intermolecular interactions, chemical reactivity, weakly bound species and applied spectroscopy.Prof. Austin J. Barnes was one of the most influential scientists in his domain of specialization, and his long scientific career has been an example to follow.